Seed germination of Genipa americana L. - Rubiaceae: temperature, substrate and post-seminal development - Andrade, Antônio Carlos Silva de; Souza, Alexandre Fadigas de; Ramos, Flavio Nunes; Pereira, Tânia Sampaio; Cruz, Ana Paula Martins (Pesquisa Agropecuaria Brasileira, 2000)
This study aimed to define the best substrate and temperature for germination of genipap (Genipa americana L. - Rubiaceae) seeds, and to describe the morphology of its seeds, post-seminal development, normal and abnormal seedlings. The experiment was designed according to a 5 x 3 factorial with constant temperatures of 20°C, 25°C, 30°C and 35°C and alternated 20°C-30°C in filter paper, vermiculite and soil substrates. The following parameters were analyzed: normal percentage germination and speed of germination. The 25°C, 30°C and 35°C temperatures and vermiculite and soil substrates were the best conditions for seed germination.